Activated Protein C Preserves Functional Islet Mass After Intraportal Transplantation - Juan L. Contreras; Christopher Eckstein; Cheryl A. Smyth; Guadalupe Bilbao; Mario Vilatobá; Sharman E. Ringland; Carlton J. Young; John A. Thompson; José A. Fernández; John H. Griffin; Devin E. Eckhoff (2004)
Clinical studies indicate that significant loss of functional islet mass occurs in the peritransplant period. Islets are injured as a result of detrimental effects of brain death, pancreas preservation, islet isolation, hypoxia, hyperglycemia, and immune-mediated events. In addition, recent studies demonstrated that islets are injured as a result of their exposure to blood and of activation of intrahepatic endothelial and Kupffer cells, resulting in inflammation and thrombosis. Activated protein C (APC) is an anticoagulant enzyme that also exerts anti-inflammatory and antiapoptotic activities by acting directly on cells. Here, we report that exogenous administration of recombinant murine APC (mAPC) significantly reduced loss of functional islet mass after intraportal transplantation in diabetic mice. Animals given mAPC exhibited better glucose control, higher glucose disposal rates, and higher arginine-stimulated acute insulin release. These effects were associated with reduced plasma proinsulin, intrahepatic fibrin deposition, and islet apoptosis early after the transplant. In vitro and in vivo data demonstrated that mAPC treatment was associated with a significant reduction of proinflammatory cytokine release after exposure of hepatic endothelial cells to islets. mAPC treatment also prevented endothelial cell activation and dysfunction elicited by intrahepatic embolization of isolated islets inherent to pancreatic islet transplantation (PIT). This study demonstrates multiple remarkable beneficial effects of mAPC for PIT and suggests that APC therapy may enhance the therapeutic efficacy of PIT in diabetic patients.